The first teresomatan caecilian (Amphibia: Gymnophiona) from the Eastern Ghats of India—a new species of Gegeneophis Peters, 1880 - Agarwal, Ishan; Wilkinson, Mark; Mohapatra, Pratyush P.; Dutta, Sushil K.; Giri, Varad B.; Gower, David J. (Zootaxa, 2013)
A new species of caecilian amphibian, Gegeneophis orientalis sp. nov., is described based on a series of nine specimens from high elevation (ca. 1,200 m) habitats in the Eastern Ghats in the states of Andhra Pradesh and Odisha, India. This species differs from all other congeners in having only bicuspid teeth in the outer as well as inner rows. The new species is the first caecilian reported from the state of Odisha, the first teresomatan caecilian from the Eastern Ghats, and is the only Indian indotyphlid known from outside the Western Ghats region.